Knowledge and use of the digital platform of institutional documents by pharmacy professionals: a diagnosis - Elice Maria SILVA; Camila Nascimento MONTEIRO; Carlos Moreira CUNHA (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective: This study analyzed the knowledge and use of the digital platform for accessing institutional documents by pharmacy professionals at a philanthropic hospital in São Paulo. Method: This is an exploratory study with a quantitative approach. The results were obtained by applying a semi-structured questionnaire to pharmacy professionals at the hospital under study, with different job titles and work shifts. Results: A total of 152 professionals were interviewed, and the majority were male (51.3%). Regarding age, they were adults with an average of 32.3 years. Knowledge of the digital platform used by the hospital was reported by 75% of the survey participants, while daily access at work was described by only 2.6%. Most interviewees described the lack of keyword recognition by the system as the main difficulty in accessing institutional documents. It was observed that 78.9% of the professionals interviewed stated that they had knowledge of the procedures in their area, while 21.1% did not. The most frequently mentioned opportunity for improvement for these documents was the text being written in a clear and direct manner (39.5%). Conclusion: Although most professionals are familiar with the platform and its function, there is low usage, which can be explained by the difficulty of accessing it, searching for documents using keywords, and the extensive format and few visual illustrations in which the documents are presented. Thus, this study can be used as information support for improvement actions in the areas of pharmacy and hospital quality management, and it is also possible to replicate this study for other sectors, seeking to obtain a broader view of this topic.